Motion – Helicobacter pylori Causes or Worsens GERD: Arguments against the Motion - Kenneth EL McColl (Canadian Journal of Gastroenterology)
Data from large epidemiological studies show that Helicobacter pylori is less prevalent in patients with gastroesophageal reflux disease (GERD) than in control subjects. The more virulent cagA-positive strains of the organism are also less commonly seen in patients with erosive esophagitis and in those with Barrett's esophagus than in those with less severe forms of GERD. Although the relationship between H pylori and gastric physiology is complex, the organism has little effect on acid secretion in most North American or Western European subjects, and has a net suppressive effect, especially in elderly subjects, in other parts of the world. Thus, the organism has a potential protective effect against GERD, which is exacerbated by gastric acidity. H pylori has no proven effect on other gastric factors that might provoke reflux, including delayed gastric emptying or inappropriate relaxation of the gastric fundus. Two well-designed interventional studies have found that eradication of H pylori either provoked GERD or had no effect. A third smaller study, which seemed to demonstrate that persistent infection was associated with GERD, was flawed, in that the two treatment groups were not comparable. The evidence thus does not support the idea that H pylori infection provokes or aggravates GERD.